Compound with electron transport function, organic light-emitting device containing compound and application of organic light-emitting device
By connecting alkyl fluorenyl and triazine side chains to compounds of organic electroluminescent materials, the problem of insufficient electron transport performance of existing materials is solved, and the effect of reducing driving voltage, improving luminescence efficiency and extending service life is achieved.
Patent Information
- Application Number
- CN202510294590.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-13
AI Technical Summary
The electron transport performance of existing organic electroluminescent materials is insufficient, resulting in high driving voltage, low luminescence efficiency and short service life.
By connecting the alkyl fluorenyl and triazine side chains to the compound, a compound with electron transport function is obtained, which is used as an electron transport layer or a hole barrier layer.
Reduces the driving voltage, improves the luminous efficiency, and extends the service life.
Smart Images

Figure CN119798236A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of organic photoelectric materials, and in particular, relates to a compound with electron transport function, an organic electroluminescent device containing the compound, and applications thereof. Background Art
[0002] With the rapid development of information technology, people have also put forward new goals and requirements for the performance of information display systems. How to give displays high brightness, high resolution, wide viewing angle and low energy consumption has become a research hotspot. At present, OLED has been gradually applied to high-end display fields such as mobile phones, wearable devices, cars and computers. More and more companies are also developing foldable and curlable OLED screens to meet people's requirements for large-screen experience and product portability.
[0003] Organic light-emitting devices convert electrical energy into light by applying electricity to organic electroluminescent materials. Organic light-emitting devices generally include an anode, a cathode, and an organic layer formed between or outside the two electrodes. The organic layer includes an electron transport material, which is responsible for regulating the injection speed and amount of electrons. For electron transport materials, they mainly transmit electrons, and usually require that their LUMO (lowest unoccupied molecular orbital) energy level is small, and generally contain electron-withdrawing groups, such as halogen, pyridine, triazine, triazole, hydroxyl, etc., which are conducive to obtaining electrons, and the LUMO energy level should match the work function of the cathode as much as possible, which can maximize the injection and transmission of electrons. At the same time, the HOMO (Highest Occupied Molecular Orbital, the energy level of the highest occupied molecular orbital) of the electron transport material should be as large as possible, which can block the transmission of holes in the light-emitting layer to the cathode, so that more holes are confined in the light-emitting layer to form excitons and generate light.
[0004] However, there are currently few materials that can be used as electron transport layers with excellent performance, especially the lifespan and luminous efficiency of organic electroluminescent materials have not been significantly improved. Therefore, it is particularly important to develop higher performance organic materials for electron transport layers and then promote the industrialization process. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a compound with electron transport function, an organic electroluminescent device containing the compound and its application, Alkylfluorene groups and triazine side chains are connected thereto, and the obtained compound can be used as a material for an electron transport layer or a hole blocking layer, and has the advantages of reducing driving voltage, improving luminous efficiency and extending service life.
[0006] In order to solve the above problems, the present invention provides the following technical solutions: In a first aspect, the present invention provides a compound having an electron transport function, which is used as an electron transport layer or a hole blocking layer. The compound having an electron transport function has a structure shown in Formula I: , Among them, at least one of X1-X3 is N, and the rest are C; Ar1, Ar2 are independently selected from the following groups which may be substituted with deuterium or not, and are substituted at the substitutable positions:
[0007] L1 is independently selected from a chemical bond, a phenyl group, a naphthyl group, a biphenyl group, and a terphenyl group substituted or unsubstituted by deuterium; X is independently selected from O, S, CR3R4, NR5, wherein R3 R5 are independently selected from deuterium-substituted or unsubstituted C1 C6 alkyl; C6 substituted or unsubstituted by deuterium C 12 Aryl; R is selected from C1-C6 alkyl which may be substituted by deuterium; Furthermore, Formula I has the structure shown in Formula a-Formula d:
[0008] Among them, there are at least two Ns in X1-X3; R is selected from the following groups which may be substituted by deuterium: methyl, ethyl, propyl, butyl, pentyl, hexyl; R3, R4 are selected from methyl substituted or unsubstituted by deuterium; R5 is selected from the following groups which may be substituted by deuterium: phenyl, naphthyl, biphenyl; Furthermore, R is selected from one or more of -CH3, -CD3, -CHD2, -CH2D, -CH2-CH3, -CD2CD3; R3, R4 are independently selected from -CH3, -CD3, -CHD2, -CH2D; R5 is selected from: ; L1 is independently selected from a chemical bond, and the following groups: ; Wherein, D is deuterium, n is an integer selected from 0-9, and * represents the connection position; In the present invention, the substitution position is defined as follows: .
[0009] In one embodiment of the present invention, the compound having electron transport function is any one of the following structures, but is not limited thereto:
[0010]
[0011]
[0012]
[0013]
[0014]
[0015]
[0016]
[0017]
[0018]
[0019]
[0020]
[0021]
[0022]
[0023]
[0024]
[0025] In a second aspect, the present invention also provides a method for synthesizing a compound having an electron transport function, which specifically comprises: Under N2 protection, reactant aI (1.0 eq) was dissolved in tetrahydrofuran (THF), magnesium (Mg) (1.0-2.0 eq) was added, and the mixture was stirred at 80-85°C for 2-4 hours. A solution of reactant bI (1.0 eq) dissolved in THF was added at 0°C, and the mixture was stirred at room temperature for 4-6 hours, and the reaction was terminated with 2M hydrochloric acid, and the reaction product was extracted with dichloromethane (CH2Cl2) and water, and the organic layer was dried with anhydrous magnesium sulfate (MgSO4) and concentrated, and the remaining substance was purified by column chromatography to obtain intermediate cI.
[0026] Under N2 protection, the intermediate cI (1.0 eq) was added with reactant dI (1.0-1.5 eq), tris(dibenzylideneacetone)dipalladium (Pd2(dba)3) (0.01-0.05 eq), potassium acetate (AcOK) (2.0-4.0 eq) and N,N-dimethylformamide (DMF), and stirred at 150-170°C for 18-24 hours. Then, the mixture was cooled to room temperature and washed with water, and the remaining substance was purified by column chromatography to obtain the intermediate eI.
[0027] Under N2 protection, the intermediate eI (1.0 eq), the reactant fI (1.0-1.4 eq), palladium acetate (Pd(OAc)2) (0.02-0.04 eq) and 2-cyclohexyl-2,4,6-triisopropylbiphenyl (X-Phos) (0.05-0.1 eq), cesium carbonate (Cs2CO3) (2.0-3.0 eq) are respectively added to a mixed solvent of toluene (Toluene), ethanol (EtOH), and water, the temperature is raised to 80-90°C, the reaction is carried out for 10-16 hours, the mixture is cooled to room temperature, H2O is added, and the solid is filtered after precipitation is complete. The remaining substance is purified by column chromatography to obtain Formula I.
[0028] Synthesis route: .
[0029] In a third aspect, the present invention further provides an organic electroluminescent device, comprising an anode, a cathode, and an organic layer arranged between the anode and the cathode; the organic layer comprises one or more of a hole injection layer, a hole transport layer, an electron blocking layer, a luminescence auxiliary layer, a luminescent layer, a hole blocking layer, an electron transport layer, an electron injection layer, and a capping layer; the hole blocking layer and / or the electron transport layer contains a compound with an electron transport function having a structure shown in the above formula I.
[0030] The structure of the organic electroluminescent device is not limited thereto, and may include fewer or more organic layers.
[0031] In one embodiment of the present invention, when manufacturing an organic electroluminescent device, the organic layer is formed by vacuum evaporation or solution coating.
[0032] In one embodiment of the present invention, the solution coating method includes one or more of spin coating, dip coating, blade coating, inkjet printing, screen printing, spraying and roller coating, but is not limited thereto.
[0033] In one embodiment of the present invention, the organic electroluminescent device is classified into a top emission type, a bottom emission type or a bi-directional emission type according to the materials used.
[0034] As the anode material, a material having a large work function is generally preferred so that holes can be smoothly injected into the organic material layer.
[0035] In one embodiment of the present invention, specific examples of anode materials that can be used include: metals such as vanadium, chromium, copper, zinc and gold, or alloys thereof; metal oxides such as zinc oxide, indium oxide, indium tin oxide (ITO) and indium zinc oxide (IZO); combinations of metals and oxides such as ZnO:Al or SnO2:Sb; conductive polymers such as poly(3-methylthiophene), poly[3,4-(ethylene-1,2-dioxy)thiophene] (PEDOT), polypyrrole and polyaniline, but are not limited thereto.
[0036] The hole injection material is a material that advantageously receives holes from the anode at a low voltage, and the highest occupied molecular orbital (HOMO) of the hole injection material is preferably between the work function of the anode material and the HOMO of the surrounding organic material layer.
[0037] In one embodiment of the present invention, the material of the hole injection layer includes metal porphyrin, oligothiophene, organic material based on aromatic amine, organic material based on hexanitrile hexaazatriphenylene, organic material based on quinacridone, organic material based on perylene, anthraquinone, and conductive polymers based on polyaniline and polythiophene, etc., but is not limited thereto, and may also include other compounds capable of p-doping.
[0038] The material of the hole transport layer is a material that can receive holes from the anode or the hole injection layer and transport the holes to the light emitting layer, and a material having high hole mobility is suitable.
[0039] In one embodiment of the present invention, the material of the hole transport layer includes an organic material based on arylamine, a conductive polymer, a block copolymer having both a conjugated part and a non-conjugated part, etc., but is not limited thereto.
[0040] The light-emitting layer can emit red, green or blue light and can be formed of a phosphorescent material or a fluorescent material. The material of the light-emitting layer is a material that can emit light in the visible light region by receiving holes and electrons from the hole transport layer and the electron transport layer respectively and combining the holes with the electrons, and is preferably a material having a favorable quantum efficiency for fluorescence or phosphorescence.
[0041] In one embodiment of the present invention, the material of the light-emitting layer includes: 8-hydroxyquinoline aluminum complex (Alq3); carbazole-based compounds; diphenylene compounds; BAlq; 10-hydroxybenzoquinoline-metal compounds; benzocarbazole-based, benzothiazole-based and benzimidazole-based compounds; poly(p-phenylene vinylene) (PPV)-based polymers; spiro compounds; polyfluorene; rubrene, etc., but are not limited thereto.
[0042] In one embodiment of the present invention, the light-emitting layer comprises a host material and a doping material.
[0043] In one embodiment of the present invention, the host material of the light-emitting layer includes condensed aromatic ring derivatives, heterocyclic compounds, and the like.
[0044] Specifically, the fused aromatic ring derivatives include anthracene derivatives, pyrene derivatives, naphthalene derivatives, pentacene derivatives, phenanthrene compounds, fluoranthene compounds, etc., and the heterocyclic compounds include carbazole derivatives, dibenzofuran derivatives, ladder-type furan compounds, pyrimidine derivatives, etc., however, the materials are not limited thereto.
[0045] In one embodiment of the present invention, the doping material of the light-emitting layer includes fluorescent doping and phosphorescent doping.
[0046] For example, it can be selected from aromatic amine derivatives, styrylamine compounds, boron complexes, fluoranthene compounds, metal complexes, and the like.
[0047] The hole blocking layer will block the holes from the anode at the interface of the device's light-emitting layer, thereby increasing the probability of recombination between electrons and holes at the interface of the device's light-emitting layer and increasing the luminescence efficiency of the device.
[0048] The compound of the structure shown in Formula I in the present invention can be used as a material for a hole blocking layer.
[0049] The electron transport layer can promote electron transport. The electron transport material is a material that advantageously receives electrons from the cathode and transports the electrons to the light-emitting layer, and preferably uses a material with high electron mobility.
[0050] The compound with the structure shown in Formula I described in the present invention can be used as an electron transport layer material.
[0051] The electron injection layer can play a role in promoting electron injection. The electron injection material is preferably a compound that has the ability to transport electrons, has an effect of injecting electrons from the cathode, has an excellent electron injection effect on the light-emitting layer or the light-emitting material, prevents the excitons generated in the light-emitting layer from migrating to the hole injection layer, and, in addition, has excellent thin film forming ability.
[0052] For example, the materials of the electron injection layer include fluorenone, anthraquinone dimethane, diphenoquinone, thiopyran dioxide, azole, diazole, triazole, imidazole, perylenetetracarboxylic acid, fluorenyl methane, anthrone and the like and their derivatives, metal complexes, nitrogen-containing 5-membered ring derivatives, etc., but are not limited thereto.
[0053] As the cathode material, a material having a small work function is generally preferred so that electrons can be smoothly injected into the organic material layer.
[0054] In one embodiment of the present invention, the cathode material includes: metals, such as magnesium, calcium, sodium, potassium, titanium, indium, yttrium, lithium, gadolinium, aluminum, silver, tin and lead, or alloys thereof; multilayer structure materials, such as LiF / Al or LiO2 / Al; and the like, but are not limited thereto.
[0055] In a fourth aspect, the present invention also provides an organic electroluminescent device for use in flat panel displays, computer monitors, medical monitors, televisions, billboards, lamps for internal or external lighting and / or signals, head-up displays, fully transparent or partially transparent displays, flexible displays, laser printers, telephones, mobile phones, tablets, photo albums, personal digital assistants (PDAs), wearable devices, laptops, digital cameras, camcorders, viewfinders, microdisplays, three-dimensional displays, virtual reality or augmented reality displays, vehicles, video walls including multiple displays tiled together, theater or venue screens, light therapy devices and signs.
[0056] Beneficial effects of the present invention: The present invention provides a compound having electron transport function. The compound is obtained by connecting an alkylfluorene group and a triazine side chain. When the compound is used as a material for an electron transport layer or a hole blocking layer, it has the advantages of reducing driving voltage, improving luminous efficiency and extending service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] Figure 1 is the H NMR spectrum of compound 40. DETAILED DESCRIPTION
[0058] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0059] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available.
[0060] Example 1 Synthesis of compound 40
[0061] CAS: Reactant a-40:70402-38-9 CAS: Reactant b-40:2087889-86-7 CAS: Reactant f-40:2260561-71-3 Under N2 protection, reactant a-40 (1.0 eq) was dissolved in THF, Mg (1.5 eq) was added, and the mixture was stirred at 85°C for 2 hours. THF and reactant b-40 (1.0 eq) were added at 0°C, and the mixture was stirred at room temperature for 4 hours, the reaction was terminated with 2M hydrochloric acid, the reaction product was extracted with CH2Cl2 and water, the organic layer was dried with anhydrous MgSO4 and concentrated, and the remaining material was purified by column chromatography to obtain intermediate c-40 (yield: 76.2%, test value MS (ESI, m / Z): [M+H]+= 380.48).
[0062] Under N2 protection, reactant d-40 (1.0 eq), Pd2(dba)3 (0.03 eq), AcOK (3.0 eq) and DMF were added to intermediate c-40 (1.0 eq) and stirred at 150 ° C for 24 hours. Then cooled to room temperature and washed with water, the remaining material was purified by column chromatography to obtain intermediate e-40 (yield: 80.6%, test value MS (ESI, m / Z): [M+H]+ = 472.35).
[0063] Under N2 protection, the intermediate e-40 (1.0 eq), reactant f-40 (1.2 eq), Pd(OAc)2 (0.02 eq) and X-Phos (0.05 eq), Cs2CO3 (2.1 eq) were added to a mixed solvent of toluene, ethanol and water, respectively, the temperature was raised to 80 °C, the reaction was carried out for 10 h, the reaction was cooled to room temperature, H2O was added, and the solid was filtered after precipitation. The remaining substance was purified by column chromatography to obtain compound 40 (yield: 83.1%, test value MS (ESI, m / Z): [M+H]+= 679.26).
[0064] The yield in each of the above steps is the fractional yield of the corresponding step.
[0065] Characterization: HPLC purity: >99.8%.
[0066] Elemental Analysis: Theoretical values: C, 84.93; H, 4.45; N, 8.25; O, 2.36 Measured values: C, 84.76; H, 4.51; N, 8.40; O, 2.39.
[0067] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of compound 40 prepared in Example 1.
[0068] Other compounds of the present application can be obtained by referring to the synthesis methods of the above-mentioned synthesis examples, so they will not be listed here one by one. The mass spectrometer model is Waters XEVO TQD, low precision, ESI source test.
[0069] Application Example 1-Application Example 82 Formula I as electron transport material for preparing organic electroluminescent devices Application Example 1 a. ITO anode: Wash the ITO (indium tin oxide)-Ag-ITO (indium tin oxide) glass substrate with a coating thickness of 150nm in distilled water twice, ultrasonically wash for 30 minutes, and then repeatedly wash it with distilled water twice, ultrasonically wash for 10 minutes. After washing, bake it in a vacuum oven at 220℃ for 2 hours. After baking, cool it down and it can be used. Use this substrate as the anode, use an evaporation machine to perform the evaporation device process, and evaporate other functional layers on it in sequence.
[0070] b. HIL (hole injection layer): Hole injection layer materials HT-1 and P-dopant were vacuum evaporated at an evaporation rate of 1 angstrom / second. The chemical formula is shown below. The evaporation rate ratio of HT-1 and P-dopant is 95:5, and the thickness is 10 nm.
[0071] c. HTL (hole transport layer): 120 nm of HT-1 was vacuum-deposited on the hole injection layer at a deposition rate of 1.5 Å / s as a hole transport layer. The chemical formula is shown below.
[0072] d. Prime (luminescence auxiliary layer): 5 nm of prime-1 was vacuum-deposited on the hole transport layer at a deposition rate of 0.5 Å / s as a luminescence auxiliary layer. The chemical formula is shown below.
[0073] e. EML (light-emitting layer): At a deposition rate of 1 angstrom / s, a host material (Host-1) and a dopant material (Dopant-1) with a thickness of 30 nm are vacuum-deposited on the light-emitting auxiliary layer as a light-emitting layer. The chemical formulas of Host-1 and Dopant-1 are shown below. The deposition rate ratio of Host-1 and Dopant-1 is 95:5.
[0074] f. HB (hole blocking layer): HB-1 with a thickness of 5.0 nm was vacuum-deposited on the light-emitting layer at a deposition rate of 0.5 Å / s as a hole blocking layer. The chemical formula of the layer is shown below.
[0075] g. ETL (electron transport layer): Compound 40 and Liq were vacuum-deposited on the hole blocking layer with a thickness of 30 nm at a deposition rate of 1 Å / s as an electron transport layer, and the deposition rate ratio of the compound 40 and Liq was 50:50.
[0076] h. EIL (electron injection layer): A Yb film layer with a thickness of 1.0 nm is evaporated on the electron transport layer at a deposition rate of 0.5 angstroms / second to form an electron injection layer.
[0077] i. Cathode: Magnesium and silver with a thickness of 13 nm were evaporated on the electron injection layer at an evaporation rate of 1 angstrom / second. The evaporation rate ratio of magnesium to silver was 1:9, to obtain a cathode.
[0078] j. Light extraction layer: CPL-1 with a thickness of 70 nm was vacuum-deposited on the cathode at a deposition rate of 1 angstrom / second as a light extraction layer. The chemical formula of CPL-1 is shown below.
[0079] k. Package the vapor-deposited substrate: first, use the glue coating equipment to coat the cleaned cover with UV glue; then move the coated cover to the pressing section, and place the vapor-deposited substrate on the upper end of the cover; finally, bond the substrate and cover with the bonding equipment, and complete the light curing of the UV glue.
[0080] The device structure is as follows: .
[0081] Application Example 2-82 The organic electroluminescent devices of Application Examples 2-82 were prepared according to the above-mentioned method for preparing an organic electroluminescent device, except that the compound 40 in Application Example 1 was replaced with a corresponding compound (as shown in Table 1) to form an electron transport layer.
[0082] Comparative Example 1-Comparative Example 10 An organic electroluminescent device was prepared according to the above-mentioned method for preparing an organic electroluminescent device, except that the compound 40 in Application Example 1 was replaced by comparative compounds 1 to comparative compounds 10, respectively, wherein the structural formulas of comparative compounds 1 to comparative compounds 10 are as follows:
[0083] The driving voltage, luminous efficiency, BI value and life of the organic electroluminescent devices obtained from the device application examples 1-82 and the device comparative examples 1-10 were characterized at a brightness of 1000 (nits). The test results are shown in Table 1 below: Table 1. Luminous characteristics test results (brightness value is 1000 nits)
[0084]
[0085]
[0086] Application Example 83-Application Example 138 Formula I is used as a hole blocking material to prepare an organic electroluminescent device: Application Example 83 a. ITO anode: Wash the ITO (indium tin oxide)-Ag-ITO (indium tin oxide) glass substrate with a coating thickness of 150nm in distilled water twice, ultrasonically wash for 30 minutes, and then repeatedly wash it with distilled water twice, ultrasonically wash for 10 minutes. After washing, bake it in a vacuum oven at 220℃ for 2 hours. After baking, cool it down and it can be used. Use this substrate as the anode, use an evaporation machine to perform the evaporation device process, and evaporate other functional layers on it in sequence.
[0087] b. HIL (hole injection layer): 1 / s evaporation rate, vacuum evaporation hole injection layer materials HT-2 and P-dopant, whose chemical formula is as follows. The evaporation rate ratio of HT-2 and P-dopant is 97:3, and the thickness is 10nm; c. HTL (hole transport layer): 1.5 / s evaporation rate, 130nm HT-2 was vacuum evaporated on the hole injection layer as a hole transport layer, and its chemical formula is as follows; d. Prime (luminous auxiliary layer): 0.5 / s evaporation rate, 5nm of prime-1 was vacuum evaporated on the hole transport layer as a light-emitting auxiliary layer, and its chemical formula is as follows; e. EML (luminescent layer): 1 / s, a main material (Host-2) and a dopant material (Dopant-2) with a thickness of 20 nm are vacuum-deposited on the light-emitting auxiliary layer as a light-emitting layer. The chemical formulas of Host-2 and Dopant-2 are shown below, and the evaporation rate ratio of Host-2 and Dopant-2 is 98:2.
[0088] f, HB (hole blocking layer): 0.5 / s evaporation rate, 169 with a thickness of 5.0nm was vacuum evaporated on the light-emitting layer as a hole blocking layer.
[0089] g, ETL (Electron Transport Layer): 1 / s, ET-2 and Liq with a thickness of 30 nm were vacuum evaporated on the hole blocking layer as an electron transport layer, and the evaporation rate ratio of ET-2 and Liq was 50:50.
[0090] h, EIL (electron injection layer): 0.5 / s, a Yb film with a thickness of 1.0 nm was evaporated on the electron transport layer to form an electron injection layer.
[0091] i. Cathode: 1 / s, magnesium and silver with a thickness of 13 nm were evaporated on the electron injection layer, and the evaporation rate ratio of magnesium to silver was 1:9, to obtain a cathode.
[0092] j. Light extraction layer: 1 / s, and CPL-2 with a thickness of 65 nm was vacuum-deposited on the cathode as a light extraction layer. The chemical formula of CPL is shown below.
[0093] k. Package the vapor-deposited substrate: first, use the glue coating equipment to coat the cleaned cover with UV glue; then move the coated cover to the pressing section, and place the vapor-deposited substrate on the upper end of the cover; finally, bond the substrate and cover with the bonding equipment, and complete the light curing of the UV glue.
[0094] Device structure:
[0095] Application Example 84-138 The organic electroluminescent devices of Application Examples 84-138 were prepared according to the above-mentioned method for preparing an organic electroluminescent device, except that the compound 169 in Application Example 83 was replaced by a corresponding compound (as shown in Table 2) to form a hole blocking layer.
[0096] Comparative Example 11-Comparative Example 17 An organic electroluminescent device was prepared according to the above-mentioned method for preparing an organic electroluminescent device, except that the compound 138 in Application Example 84 was replaced by comparative compounds 11 to comparative compounds 17, respectively, wherein the structural formulas of comparative compounds 11 to comparative compounds 17 are as follows:
[0097] The driving voltage, luminous efficiency, BI value and life of the organic electroluminescent devices obtained from the device application examples 83-138 and the device comparative examples 11-17 were characterized at a brightness of 1000 (nits). The test results are shown in Table 2 below: Table 2 Luminous characteristics test results (brightness value is 1000 nits)
[0098]
[0099] Those skilled in the art will know that in a blue top-emitting device, the luminous efficiency is greatly affected by chromaticity. Therefore, the influence of chromaticity on efficiency is taken into account, and the ratio of luminous efficiency to CIEy is defined as the BI value, that is, BI = (cd / A) / CIEy.
[0100] The compounds of the present invention are , an alkylfluorenyl group and a triazine side chain are connected thereto. From the data in Table 1 and Table 2, the compound material with the structure shown in Formula I provided by the present invention is used as an electron transport or hole blocking layer in an organic electroluminescent device. Compared with the device prepared by the comparative compound 1-17, the driving voltage, BI and life are all improved.
[0101] Specifically, the difference between the comparative compounds 8, 9, and 10 and the compounds 1, 397, and 87 of the present invention is that the comparative compounds 8, 9, and 10 are connected to 9-phenylfluorene groups, while the compounds of the present invention are 9-alkyl (methyl) fluorene groups. The aromatic groups of the phenylfluorene groups in the comparative examples do not play a conjugated role, but increase the molecular weight of the compounds, and the evaporation temperature will be higher, which is easy to cause material decomposition and affect the life of the device. The position of the triazine side chain affects the mobility of the side chain, and thus affects the efficiency of the device.
[0102] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A compound having an electron transport function, characterized in that: The compound has the general structural formula shown in Formula I: , Among them, at least one of X1-X3 is N, and the rest are C; Ar1, Ar2 are independently selected from the following groups which may be substituted with deuterium, and are substituted at the substitutable position: ; L1 is independently selected from a chemical bond, a phenyl group, a naphthyl group, a biphenyl group, and a terphenyl group substituted or unsubstituted by deuterium; X is independently selected from O, S, CR3R4, NR5, wherein R3 R5 are independently selected from deuterium-substituted or unsubstituted C1 C6 alkyl; C6 substituted or unsubstituted by deuterium C 12 Aryl; R is selected from C1-C6 alkyl groups which may be substituted by deuterium.
2. The compound having electron transport function according to claim 1, characterized in that The formula I has the structure shown in formula a-formula d: Among them, there are at least two Ns in X1-X3; R is selected from one or more of methyl, ethyl, propyl, butyl, pentyl and hexyl substituted or unsubstituted by deuterium; R3, R4 are selected from methyl substituted or unsubstituted by deuterium; R5 is selected from phenyl, naphthyl and biphenyl which may be substituted by deuterium.
3. The compound having electron transport function according to claim 2, characterized in that R is selected from one or more of -CH3, -CD3, -CHD2, -CH2D, -CH2-CH3, -CD2CD3; R3, R4 are independently selected from -CH3, -CD3, -CHD2 or -CH2D; R5 is selected from: ; Wherein, D is deuterium, n is an integer selected from 0-9, and * represents the connection position.
4. The compound having electron transport function according to claim 2 or 3, characterized in that L1 is independently selected from a chemical bond and the following groups: ; Wherein, D is deuterium, n is an integer selected from 0-9, and * represents the connection position.
5. The compound having electron transport function according to claim 1, characterized in that The compound is any one of the following structures: 。 6. A method for synthesizing the compound having electron transport function according to any one of claims 1 to 5, characterized in that: The following steps are involved: Under N2 protection, 1.0 eq of reactant aI was dissolved in tetrahydrofuran, 1.0-2.0 eq of magnesium was added, and stirred at 80-85°C for 2-4 hours; A 1.0 eq solution of the reactant bI dissolved in THF was added at 0°C, and the mixture was stirred at room temperature for 4-6 hours, the reaction was terminated with 2M hydrochloric acid, the reaction product was extracted with dichloromethane and water, the organic layer was dried over anhydrous magnesium sulfate and concentrated, and the remaining substance was purified by column chromatography to obtain intermediate cI; Under N2 protection, add 1.0 eq of dI, 0.01-0.05 eq of tris(dibenzylideneacetone)dipalladium, 2.0-4.0 eq of potassium acetate and N,N-dimethylformamide to 1.0 eq of intermediate cI, stir at 150-170°C for 18-24 hours, then cool to room temperature and wash with water, purify the remaining substance by column chromatography to obtain intermediate eI; Under N2 protection, 1.0 eq of intermediate eI, 1.0-1.4 eq of reactant fI, 0.02-0.04 eq of palladium acetate, 0.05-0.1 eq of 2-cyclohexyl-2,4,6-triisopropylbiphenyl, and 2.0-3.0 eq of cesium carbonate were added to a mixed solvent of toluene, ethanol, and water, respectively, and the temperature was raised to 80-90° C., reacted for 10-16 h, cooled to room temperature, and H2O was added. After solid precipitation was completed, it was filtered, and the remaining substance was purified by column chromatography to obtain a compound with an electron transport function of the structure shown in Formula I; The synthetic route is as follows: 。 7. An organic electroluminescent device, characterized in that: It comprises an anode, a cathode and an organic layer arranged between the anode and the cathode; the organic layer comprises one or more of a hole injection layer, a hole transport layer, an electron blocking layer, a luminescence auxiliary layer, a luminescent layer, a hole blocking layer, an electron transport layer, an electron injection layer and a capping layer; the hole blocking layer and / or the electron transport layer contains the compound with electron transport function as claimed in any one of claims 1 to 5.
8. The organic electroluminescent device according to claim 7, characterized in that: The organic layer is formed by vacuum evaporation or solution coating; the solution coating method includes one or more of spin coating, dip coating, blade coating, inkjet printing, screen printing, spraying and roller coating.
9. The organic electroluminescent device according to claim 7, characterized in that: The material of the hole injection layer includes one or more of metal porphyrin, oligothiophene, arylamine-based organic material, hexanitrile hexaazatriphenylene-based organic material, quinacridone-based organic material, perylene-based organic material, anthraquinone, and polyaniline-based and polythiophene-based conductive polymers; The material of the hole transport layer includes an arylamine-based organic material, a conductive polymer, or a block copolymer having both a conjugated portion and a non-conjugated portion.
10. An organic electroluminescent device according to any one of claims 7 to 9, for use in flat panel displays, computer monitors, medical monitors, televisions, billboards, lamps for interior or exterior lighting and / or signaling, head-up displays, fully transparent or partially transparent displays, flexible displays, laser printers, telephones, mobile phones, tablets, photo albums, personal digital assistants, wearable devices, laptops, digital cameras, video cameras, viewfinders, microdisplays, three-dimensional displays, virtual reality or augmented reality displays, vehicles, video walls comprising multiple displays tiled together, theater or stadium screens, light therapy devices and signs.
Citation Information
Patent Citations
Organic compound, and organic electroluminescent device and electronic device using same
CN114716443A
Heating apparatus for heating mattress
KR1020230127707A
KR20220014504A
Cited By
Material with electron transmission function, organic electroluminescent device and application
CN121517401A